2017
DOI: 10.1177/1948550617746463
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Positivity of Migrant Stereotype Content

Abstract: Complementing well-established antecedents of anti-migrant opinion (e.g., threat), we investigated how system-sanctioned ideologies—that is, the collection of beliefs and values espoused by the government in power—are linked with migrant stereotypes. Using Canada as a case study, across three waves of national survey data ( N = 1,080), we found that system-sanctioned pro-migrant ideologies corresponded with (relatively) more positive migrant stereotype content (i.e., increases in perceived warmth and competenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…In line with this interpretation of the findings, Gaucher et al (2018) found in a longitudinal study that warmth and competence stereotypes of migrants and refugees (rated from the perspective of "most Canadians") became more positive following a change in government and related changes in political rhetoric and policies toward refugees. This change was stronger among individuals motivated to justify their sociopolitical system.…”
Section: Discussionsupporting
confidence: 64%
“…In line with this interpretation of the findings, Gaucher et al (2018) found in a longitudinal study that warmth and competence stereotypes of migrants and refugees (rated from the perspective of "most Canadians") became more positive following a change in government and related changes in political rhetoric and policies toward refugees. This change was stronger among individuals motivated to justify their sociopolitical system.…”
Section: Discussionsupporting
confidence: 64%
“…Although we had hypothesized a negative association, there are likely instances wherein a positive association would exist. Whereas system justification was long thought of as a motivation to resist changes to psychologically-important social systems, recent work finds that even high system justifiers may support social change if it seems consistent with the system's values and ideals (e.g., Calogero & Tylka, 2014;Feygina, Jost, & Goldsmith, 2010;Gaucher, Friesen, Neufeld, & Esses, 2018;Jost, 2015). Future research could also use context-specific system justification scales.…”
Section: Discussionmentioning
confidence: 99%
“…People's attitudes toward social groups and issues can shift based on various factors, such as increased familiarity with or knowledge about the issue (Neufeld, Boese, Starzyk, & Efimoff, 2019). The views of a prominent leader can also produce corresponding shifts in public attitudes, resulting from normative shifts (Crandall, Miller, & White II, 2018) or the motivation to justify the system the leader represents (Gaucher et al, 2018). Future research should explore whether the PSM is sensitive to such changes.…”
Section: Discussionmentioning
confidence: 99%
“…These policy decisions might in turn affect public opinions about the newcomers. Indeed, a recent study by Gaucher, Friesen, Neufeld, and Esses (2018) showed that system-sanctioned pro-migrant ideology of the government in power can affect public opinions of migrants. Thus, the political rhetoric around these labels may influence people's attitudes toward the different groups.…”
Section: Practical Implicationsmentioning
confidence: 99%